Development of Stunting Prevention Behavior Model Based on Health Promotion Model and Social Capital in The Magetan District - Agung Suharto; Moh. Wildan; Tinuk Esti Handayani (Humanistic Network for Science and Technology (HNST), 2020)
Background, stunting was a chronic malnutrition problem that is caused by a lack of nutrition in a long time due to food that is not in accordance with nutritional needs. The purpose was to prove the development of a health promotion model and social capital in improving the behavior of mothers of to toddlers in stunting prevention. Method, phase 1 were cross sectional, with multistage sampling, size 300 people. Exogenous variables were health promotion model and social capital, endogenous variables: stunting prevention behavior. Phase 2 were quasy experiment, sample size 100 people were 2 groups: intervention and control. Data analysis: univariate and multivariate: CFA and SEM and T Test. Results and discussion: phase 1 were significant value of T Value> 1.96, namely prior related behavior, personal factor, perceived self efficacy, Activity Related Affect.. Social capital variables significant was participation. Stage 2, intervention mean was higher than control. Independent T Test post test of the intervention and control groups with results p = 0.00 (p